Estudo experimental do comportamento mecânico de areias carbonáticas da Costa Nordeste do Brasil - Alves, Victor Luiz da Silva (2024)
The development of technologies aimed at generating energy in offshore areas has the challenge of dealing with the presence of carbonate soils in coastal regions, which reveals the importance of investigating the behavior of this type of soil. In Brazil, offshore wind farm projects with prospects for implementation on the northeastern coast have demanded research aimed at analyzing the particularities of this type of material, since detailed studies on the geotechnical behavior of carbonate soils in this region are scarce. Therefore, this research aims, through laboratory tests, to study and compare the behavior of three sands from the coast of the state of Ceará, in northeastern Brazil. The three soil samples collected for this research consist of sands with different mineralogical compositions, being a quartz sand from the mouth of the Pacoti River in the municipality of Aquiraz-CE, a carbonate sand with 48.81% of calcium carbonate, from the mouth of the Aracatiaçu River in the municipality of Amontada-CE and a carbonate sand with 88.46% of calcium carbonate, obtained in an offshore environment at Moitas beach in Amontada-CE. To analyze the characterization and chemical compositions of the samples, particle size analysis, maximum and minimum void ratios, specific gravity, X-ray fluorescence and microscopy were performed. Subsequently, in order to study the shear strength behavior, the samples were used to reconstitute specimens for direct shear and triaxial tests drained at normal and confining stresses of 50, 100 and 200 kPa. In general, the results of the shear resistance tests show that, for the carbonate sands tested, the failure stress increases with the calcium carbonate content, on the other hand, for the same normal or confining stress, the quartz sand presented intermediate failure stress between the two carbonate sands. Regarding the strength envelopes, the differences observed between the three sands not only demonstrate the complexity of the analyses of carbonate soils, but also suggest that mineralogy has an influence on the shear strength parameters.